The effect of luminance on distance visual performance / Nur Athirah Md Adnan - Md Adnan, Nur Athirah (Faculty of Health Sciences, 2015)
Reading under different luminance level has profound effects on reading performance. However, the effects on reading performance at distance reading were remains to be determined. To investigate this issue, the performance of reading rate at distance was assessed toward difference luminance. Twenty-two (22) normally sighted university students aged 18 to 25 years old were recruited in this research. The subjects were asked to read aloud four different texts with luminance of 25%, 50%, 75%, and 100% in random order at 6 m. The time taken to complete each text was recorded and any reading error made was noted. The reading speed was measured in words per minute (wpm). The reading rate was increased from L25% to L75% (M= -12.83, 95% CI [-19.06,-6.60]), from L50% to L75% (M= -14.77, 95% CI [-23.37,-6.17]), and from L100% to L75% (M= - 18.52, 95% CI [-28.15,-8.90]). The peak was found at 75% luminance. These findings indicate that 75% luminance levels promote good reading performance in normally sighted university students.